ANALISIS KONFLIK TOKOH UTAMA DALAM ROMAN BUKAN PASAR MALAM KARYA PRAMOEDYA ANANTA TOER - Lisnasari, Dwi; Wartiningsih, Agus; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: Bukan pasar malam romance tells about sacrifice of a child for the recovery of his/her father and his/her struggle to live under economic difficulties. The problem statement are the main character internal and external conflict in Bukan Pasar Malam story by Pramoedya Anata Toer. This research aims to obtain description of conflict in Bukan Pasar Malam romance. This research aims to obtain description of conflict in Bukan Pasar Malam story. Theories which used in this research are definition of romance, elements of novel builder, internal and external conflict and literature study. This research uses descriptive method in qualitative form. Structural approach is used in this research. The data source is Bukan Pasar Malam romance and the data are words, phrases, sentences or citation that represent conflict in Bukan Pasar Malam romance. Data analysis is done by determining theinternal dan external conflict then the data is described and interpreted based on existing problems. Based on data analysis, this research gives following conclusions (a) Internal conflict in Bukan Pasar Malam romance are restless, disappointed, dislike, sad, confused, hesitant, angry, sorry, scared, wonder, nervous, bored (b) main character external conflict are debates, arguments, disputes, and misunderstandings between the main character and other figures in Bukan Pasar Malam story romance by Pramoedya Anata Toer. The result of this study is expected to be useful for readers, especially high school Indonesia Languange teachers. For college students, this research can be used as reference to conduct further research for different aspectsÂ Key words: Main Character Conflict, Novel.